Analysis of Product Image and Product Authenticity of Batik Tanah Liek towards Purchase Decision Process through Perceived Value as Intervening Variables in Padang City - Salmi, Gina Hayatul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the product image and product authenticity on the purchase decision process Batik Tanah Liek through perceived value as an intervening variable. The study was conducted on 185 respondents in Padang City who have made a decision at least once in purchasing Batik Tanah Liek. Sampling technique used is purposive sampling. Survey methods used to obtain primary data by distributing questionnaires. Data was analyzed by Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this study showed that the product image had no effect on the purchase decision process.  Meanwhile, product authenticity has a positive and significant effect on the purchase decision process. Testing intervening variables on perceived value to the purchase decision process, has a positive and significant effect.